The Expense of Insulin in Individuals with Insulin-Dependent Diabetes in Fars Province based on Prescribed Prescriptions including Insulin - Sanaz Amiri; Alireza Mirahmadizadeh; Saeed Seyfi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Diabetes is considered one of the most prevalent chronic diseases in the world, and if it is not cured, it can have many side effects and expenses. The current study has been conducted to calculate the cost of insulin applied in patients with insulin-dependent diabetes who are younger than 19 years old in 2016 and 2017. Methods: The current study is a descriptive and cross-sectional study We investigated all registered prescriptions of social security and health insurance in this study. The price of each insulin was calculated through the official website of the Food and Drug Administration (FDA). Ultimately, the cost of insulin has been calculated based on gender, age group, and insurance types under the age of 19 in patients with insulin-dependent diabetes and those without insulin-dependent diabetes. Data has been analyzed using SPSS24. The frequency command is used to obtain the percentages. Results: In this study, 1135105 insured cases younger than 19 years old were investigated, which females consisted almost half of the insured cases (51 %), and most of them were in the age group of 2-7 years (34 %), and 50 % of the participants in this study were covered by social security insurance. The treatment of each patient with insulin-dependent diabetes included a cost of $ 1187 and $ 1309, respectively, in 2016 and 2017, and $ 1.4 and $ 1.7 respectively (1$ = 42,000 Rials), for each person under the age of 19 in the general population. Conclusion: The results achieved by the mentioned study explained that nearly remarkable cost is spent on preparing insulin for patients with Type 1 Diabetes Mellitus every year. This amount is increasing, and it is essential to predict insulin needs for the future according to the insulin consumption changes.